2011
DOI: 10.1007/s00216-011-4798-5
|View full text |Cite
|
Sign up to set email alerts
|

In situ laser-induced photochemical silver substrate synthesis and sequential SERS detection in a flow cell

Abstract: A new, simple, and effective approach for multianalyte sequential surface-enhanced Raman scattering (SERS) detection in a flow cell is reported. The silver substrate was prepared in situ by laser-induced photochemical synthesis. By focusing the laser on the 320 μm inner diameter glass capillary at 0.5 ml/min continuous flow of 1 mM silver nitrate and 10 mM sodium citrate mixture, a SERS active silver spot on the inner wall of the glass capillary was prepared in a few seconds. The test analytes, dacarbazine, 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Thus, the SERS bands of citrate previously reported by us [3132] during the laser induced synthesis of SERS-active silver spots using silver nitrate-citrate mixtures can easily be explained by the presence of excess of Ag + in the solution, which induces the chemisorption of citrate onto the metal silver surface.…”
Section: Resultsmentioning
confidence: 71%
“…Thus, the SERS bands of citrate previously reported by us [3132] during the laser induced synthesis of SERS-active silver spots using silver nitrate-citrate mixtures can easily be explained by the presence of excess of Ag + in the solution, which induces the chemisorption of citrate onto the metal silver surface.…”
Section: Resultsmentioning
confidence: 71%
“…The silver substrate was situated on an integrated ITO electrode and after the sample introduction a 100 V potential pulse was applied resulting in a significant decrease of the memory effect. The recovery of the SERS substrate could be also reached within a few minutes in flow conditions on silver spots created by in situ photo‐induced reduction of NPs precursors . The small surface area resulted in relatively fast adsorption and desorption (typically several minutes) of the analyte molecules to/from the silver surface and represents promising approach toward SERS coupling with liquid‐based separation methods.…”
Section: In‐solution Strategymentioning
confidence: 99%
“…One is the in-situ fabrication of SERS-active metallic micro/nanostructures inside a microfl uidic channel, and the other is the construction of microfl uidic channels on top of the SERS substrates. [103][104][105][106] The femtosecond laser direct writing (FsLDW) technique is recognized as a powerful nanofabrication tool that could fabricate 3D complex nanostructures on a wide range of materials. Takahashi et al reported the integration of a 3D Au photonic crystal (PC) structure through the co-assembly of Au colloidal nanoparticles and large PS nanospheres inside a microfl uidic channel.…”
Section: Integration Of Solid-state Sers Substrates With Microfl Uidimentioning
confidence: 99%